2011
DOI: 10.1111/j.1365-2052.2011.02258.x
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the quantitative trait loci for milk production traits on BTA6

Abstract: A parallel association study was performed in two independent cattle populations based on 41 validated, targeted single nucleotide polymorphisms (SNPs) and four microsatellite markers to re-evaluate the multiple quantitative trait loci (QTL) architecture for milk performance on bovine chromosome 6 (BTA6). Two distinct QTL located in the vicinity of the middle region of BTA6, but differing unambiguously regarding their effects on milk composition and yield traits were validated in the German Holstein population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…PPARGC1A has been shown to play a pivotal role in the regulation of cellular energy metabolism, such as hepatic gluconeogenesis with response to fasting and food deprivation in other species (59,61), and to be a key gene in mitochondrial oxidative phosphorylation metabolism (43,51,58). In our previous studies, polymorphisms in the bovine PPARGC1A gene were found to be associated with milk performance traits in GH populations (73,74). In the present study, hepatic PPARGC1A mRNA abundance showed correlations to transcripts of genes included in the gluconeogenesis pathway and INSR, but not to MY.…”
Section: Resultsmentioning
confidence: 98%
“…PPARGC1A has been shown to play a pivotal role in the regulation of cellular energy metabolism, such as hepatic gluconeogenesis with response to fasting and food deprivation in other species (59,61), and to be a key gene in mitochondrial oxidative phosphorylation metabolism (43,51,58). In our previous studies, polymorphisms in the bovine PPARGC1A gene were found to be associated with milk performance traits in GH populations (73,74). In the present study, hepatic PPARGC1A mRNA abundance showed correlations to transcripts of genes included in the gluconeogenesis pathway and INSR, but not to MY.…”
Section: Resultsmentioning
confidence: 98%
“…ABCG2 plays an important role in the transport of nutrients into milk, especially riboflavin (vitamin B 2 ) [36] and has been identified as the candidate gene underlying a quantitative trait locus on bovine chromosome 6 that affects milk yield and composition [37,38]. Therefore, the down-regulation of ABCG2 in quarters neighbouring E. coli infected quarters may be associated with the decrease in milk yield and casein synthesis, which was observed in these animals [10,39] and may imply a nutrient deficiency in milk from these animals.…”
Section: Discussionmentioning
confidence: 99%
“…Y581S SNP is widely spread in some bovine breeds, reaching a frequency of 20% in the Israeli Holstein population (Ron et al, 2006), and it has been suggested as the causative polymorphism of a quantitative trait locus affecting the production of milk and its protein and fat composition (Cohen-Zinder et al, 2005;Weikard et al, 2012). In addition, a correlation has been suggested between this SNP and fertility (Komisarek and Dorynek, 2009).…”
Section: Introductionmentioning
confidence: 99%